Entity-level Greenhouse Gas Emission of University of Science and Technology of Southern Philippines-Oroquieta (American Journal of Environment and Climate, 2022)
Presently, climate change is still one of the pressing environmental concerns in the world generally caused by greenhouse gas emission. Among the greenhouse gases emitted by various sources, carbon dioxide contributes largely to the emission. In this study, the entity-level greenhouse gas emission of the University of Science and Technology of Southern Philippines-Oroquieta for Year 2020 was estimated following the 2006 IPCC Guidelines for National Greenhouse Gas Inventories. Based on the results, emission from mobile combustion sources was estimated to be 0.0895 tCO2e while emission from stationary combustion sources was 0.139 tCO2e yielding a total GHG emission for Scope 1 of 0.2285 tCO2e. Moreover, the electricity consumption of the campus which corresponds to the Scope 2 emission yielded 24.7135 tCO2 constitutes largely to the overall greenhouse gas emission. This might be due to the flexible learning modality where faculty members stay at their respective offices to conduct their classes hence regularly utilizing electricity from air conditioners, computers, mobile phones and others.